Sarcocystis muricoelognathis Qin & Ortega-Perez & Wibbelt & Lakim & Ginting & Khoprasert & Wells & Hu & Jäkel 2024, sp. nov. - Qin, Tao; Ortega-Perez, Paula; Wibbelt, Gudrun; Lakim, Maklarin B.; Ginting, Sulaiman; Khoprasert, Yuvaluk; Wells, Konstans; Hu, Junjie; Jäkel, Thomas (Zenodo, 2024)
Taxonomic summary of Sarcocystis muricoelognathis sp. nov. ( Sarcocystis sp.: Figs. 1, 2, 3, 4, 5, 6, Additional file 1: Table S1). Diagnosis Oocyst containing two sporocysts with four sporozoites each; sporocysts measuring on average 10.1–10.3 × 7.2– 7.5 µm; sarcocysts microscopic with striated cyst wall in fresh preparations (similar to S. singaporensis but cyst wall protrusions not resting on stalks), cigar-shaped with slightly pointed ends in older cysts; in skeletal musculature except heart; native sarcocysts in rats infected experimentally for 5 months measured 400–700 × 70–90 µm, in wild-caught rats 770–1580 × 87–123 μm; cyst wall with palisade-like, villar protrusions, 8 to 11 µm long and 2–4 µm wide at their base; protrusions at the tips of the sarcocyst often longer, 10–16 µm; banana-shaped, live cystozoites on average 5.9–6.5 µm long and 2.1–2.2 µm in diameter; ultrastructurally, villar protrusions palisade-like, attached upright to the cyst (if not bent by preparation), sometimes slightly broadened towards the apical ends, delimited by a knob-like lining and filled with fine, electron-light granular material; cystozoites with only two rhoptries throughout distribution range. Type natural definitive hosts Coelognathus radiatus (holotype), Coelognathus flavolineatus (paratype). Type experimental intermediate host Rattus norvegicus (holotype) Type natural intermediate hosts Maxomys whiteheadi (paratype); Rattus norvegicus (paratype) Type localities Holotype: central Bangkok, Tailand; paratypes: Chumphon, southern Tailand; Poring Hot Springs, Northern Borneo, Sabah, Malaysia; Anning and Nanjian Prefectures, China. Other locations and natural hosts not included in type series Sarcocysts with the same ultrastructure recorded from Rattus argentiventer and Bandicota indica in Tailand [2] and reported from Rattus rattus in Singapore [15]. Etymology Species name in reference to the intermediate and definitive hosts. Type specimens deposited Holotype deposited at the Department of Parasitology, University of ...